1998
DOI: 10.1177/089826439801000303
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Self-Rated Health among 55- to 89-Year-Old Dutch People

Abstract: The aim of this study was to examine the effects of physical activity and the possible mediating role of perceived physical self-efficacy (PPSE) on self-rated health (SRH) in the 55- to 89-year-old Dutch population. The data are based on a structured interview carried out in a random sample of 120 subjects--60 men and 60 women with the average ages of 69 and 71 years, respectively--in Sassenheim, the Netherlands, as a pilot study of the Longitudinal Aging Study Amsterdam (LASA). The results of linear multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Although linear regression is regarded as more appropriate for a continuous outcome variable, it is recognized as a robust method for even dichotomous variables 25 and has been used elsewhere with SRH as the dependent variable. [26][27][28] As a verification of our results we repeated all of our analyses using binary logistic regression (dichotomizing SRH into 'positive' (excellent, very good, good) vs. negative ('fair', 'poor')). The results obtained in this way did not materially differ from the linear regression analyses.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although linear regression is regarded as more appropriate for a continuous outcome variable, it is recognized as a robust method for even dichotomous variables 25 and has been used elsewhere with SRH as the dependent variable. [26][27][28] As a verification of our results we repeated all of our analyses using binary logistic regression (dichotomizing SRH into 'positive' (excellent, very good, good) vs. negative ('fair', 'poor')). The results obtained in this way did not materially differ from the linear regression analyses.…”
Section: Discussionmentioning
confidence: 83%
“…Finally, the use of parametric methods (linear regression) on ordinal data in our analysis is a limitation, but, as reported earlier, the same approach has been used elsewhere. [26][27][28] As a check on our results, the linear model was replicated using binary logistic regression with the dependent variable dichotomized into positive vs. negative SRH. Both linear and logistic regression models provided results not materially different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…15,19 In this study, subjects were less likely to report their fair or poor health as alcohol consumption or physical activity increased, which is consistent with previous studies. [10][11][12][13] Although being overweight was associated with self-reported fair or poor health in Western populations, 14,21 we found that the lean group (BMI<18.5) had a significant association with self-reported fair or poor health. Lee, et al 35 reported that overweight men had an elevated risk of all-cause mortality and no evidence of excess risk among lean men.…”
Section: Stratified Analysis By Study Areamentioning
confidence: 84%
“…First, PF levels are positively related to SRGH (Jylha et al 1986;Parkatti et al 1998). Studies often show that PF can explain more than 10% of the variance in SRGH (Hoeymans et al 1997a).…”
Section: Introductionmentioning
confidence: 95%